The increased risk of microvascular complications in South Asians with type 1 diabetes is influenced by migration. Issue 12 (28th November 2019) - Chetan, M.R.; Miksza, J.K.; Lawrence, I.; Anjana, R.M.; Unnikrishnan, R.; Amutha, A.; Shanthi Rani, C.S.; Jebarani, S.; Mohan, V.; Khunti, K.; Narendran, P.
Abstract: Aim: We aimed to explore the association between South Asian ethnicity and complications of type 1 diabetes, and whether this is affected by migration. Methods: In this retrospective cohort study, data on diabetes control and complications were obtained for South Asians in India (South AsiansIndia, n  = 2592) and the UK (South AsiansUK, n  = 221) and white Europeans in the UK ( n  = 1431). Multivariable logistic regression was used to identify associations between ethnicity and diabetic kidney disease, retinopathy and neuropathy adjusting for age, sex, BMI, disease duration, HbA1c, blood pressure (BP) and cholesterol. Results: South AsiansIndia had significantly greater adjusted odds of diabetic kidney disease [odds ratio (OR) 5.0, 95% confidence intervals (CI) 3.6–7.1] and retinopathy (OR 1.8, 95% CI 1.2–2.5), but lower odds of neuropathy (OR 0.5, 95% CI 0.4–0.6) than white Europeans. South AsiansIndia had significantly greater adjusted odds of diabetic kidney disease (OR 3.0, 95% 1.8–5.3) than South AsiansUK, but there was no significant difference in the odds of other complications. Conclusions: In this hypothesis‐generating study, we report that South Asian ethnicity is associated with greater risk of diabetic kidney disease and retinopathy, and lower risk of neuropathy than white European ethnicity. Part of the excess diabetic kidney disease risk is reduced in South AsiansUK . These associations cannot be accounted for by differences in vascular risk factors. Our findings in South Asians with type 1 diabetes mirror previous findings in type 2 diabetes and now need to be validated in a study of the effect of ethnicity on type 1 diabetes complications where healthcare is provided in the same setting. What's new?: The impact of South Asian ethnicity and migration on the natural history of type 1 diabetes is not well understood. South Asians in India have a greater risk of retinopathy and diabetic kidney disease and lower risk of neuropathy than white Europeans in the UK. The excess risk of diabetic kidney disease is mitigated for South Asians in the UK. These associations persist despite adjusting for classical risk factors for microvascular complications such as glycaemic control, blood pressure, disease duration or markers of insulin resistance. The results call for us to be particularly vigilant for the complications of type 1 diabetes in South Asians.